Impact of smoking on cardiovascular outcomes in patients with stable coronary artery disease. (28th April 2020) - Bouabdallaoui, Nadia; Messas, Nathan; Greenlaw, Nicola; Ferrari, Roberto; Ford, Ian; Fox, Kim M; Tendera, Michal; P Naidoo, Datshana; Hassager, Christian; Gabriel Steg, P; Tardif, Jean-Claude; ,
Abstract: Aims: Smoking is a major preventable risk factor for cardiovascular disease and mortality. However, the 'smoker's paradox' suggests that it is associated with better survival after acute myocardial infarction. We aimed to investigate the impact of smoking on mortality and cardiovascular outcomes in patients with stable coronary artery disease. Methods: The international CLARIFY registry included 32, 703 patients with stable coronary artery disease between 2009 and 2010. Among the 32, 378 patients included in the present analysis, Cox proportional hazards models (adjusted for age, sex, geographic region, prior myocardial infarction, and revascularization status) were used to estimate associations between smoking status and outcomes. Patients were stratified as follows: 41.3% of patients never smoked, 12.5% were current smokers and 46.2% were former smokers. Results: Current smokers were younger than never-smokers and former smokers (59 vs . 66 and 64 years old, respectively, p  < 0.0001). There were more men among current or former smokers compared with never-smokers. Compared with never-smokers, both current and former smokers were at higher risk of all-cause death (hazard ratio = 1.96 and 1.37) and cardiovascular death (hazard ratio = 1.92 and 1.38) within five years (all p  < 0.05). Similarly graded and increased risks were present for myocardial infarction and the composite of cardiovascular death, myocardial infarction and stroke (all p  < 0.05). Conclusion: In contrast to the 'smoker's paradox', current smokers with stable coronary artery disease have a greatly increased risk of future cardiovascular events, including mortality, compared with never-smokers. In former smokers, cardiovascular risk remains elevated albeit at an intermediate level between that of current and never-smokers, reinforcing the importance of smoking cessation. (ISRCTN43070564).